Nudging in Education - Mette Trier Damgaard; Helena Skyt Nielsen (Institute of Labor Economics (IZA), 2018)
Can we nudge children, adolescents and their parents to make better decisions on education? And can we nudge teachers to support and encourage better decision making? Education decisions are taken at young ages and involve immediate costs and potential, future benefits. In such settings behavioural barriers (e.g. lack of self-control, limited attention and social norms) likely influence choices and this may motivate the use of low cost 'nudges' to gently push behaviour in the desired direction. Our review of nudging interventions shows that while nudging often has positive effects, the greatest effects often arise for individuals affected most by the behavioural barrier targeted by the intervention. Hence understating underlying behavioural mechanisms is crucial. Negative effects may arise in situations where nudges potentially crowd-out intrinsic motivation, if nudges pressurise individuals, or in situations where the choice architect has an insufficient understanding of behavioural mechanisms.
Keywords: D03; D04; I20; 330; behavioural bias; boost policies; human capital investment